Mental health, confinement, and coronavirus concerns: a qualitative study - Vásquez, Gabriela; Urtecho-Osorto, Óscar Rolando; Agüero-Flores, Maitée; Díaz Martínez, Miguel José; Paguada, Rosa María; Varela, Melody Anette; Landa-Blanco, Miguel; Echenique , Yaraní (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
This qualitative study explores the meanings and experiences of COVID-19 concerns, confinement and its relationship to mental health. It included 20 semi-structured interviews to 10 men and 10 women. It was found that there´re people concerned about their own health and their loved ones´. This can trigger psychosomatic reactions and anxiety. Other people underestimate the graveness of COVID-19 because they don´t consider themselves vulnerable. To be recurrently exposed to media information is stressful, so some people avoid it. Economic concern is also relevant due to reduced access to labor market and the suspension or decrease of income. Some informants are experiencing alterations in their eating and sleeping habits. Even though confinement limits leisure events, the informants have engaged in individual and familiar recreational activities.